(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2015)
Park’s Dendroflora includes 115 species (101 kultigenofits, 14 spontanofits) and 9 decorative forms of plants from 77 genera and 40 families. This variety is higher than in the most of reserve parks dendroflora in the Odessa region. Leading families are Rosaceae (22,8 % of species), Pinaceae, Aceraceae, Oleaceae, Vitaceae, Cupressaceae (from 7.0 to 4,4 %), leading genera are Acer (7 species) and Rosa (6 species). Among the 12 life-forms (after I.G.Serebryakov) deciduous upright trees (52 species, 46,6 %) and shrubs (33 species, 28,9 %) are dominating. Though Circumboreal ranges are dominant (37,7 %), Asian (24,6 %) and North American (23,7 %) elements play significant role. 15 plant species included in the Red List of the International Union for Conservation of Nature. We propose to include the park in the natural reserve fund of the Odessa region in the category of "park-monument of landscape art of local significance."